Preconceito racial e programa bolsa família: o papel mediador do preconceito racial na relação entre a cor da pele da família beneficiária e o nível de apoio a esse Programa - Freitas, Hévilla Rodrigues de (2019)
This dissertation aims to analyze the mediating role of racial prejudice in the relation between the skin color of the beneficiary family and the level of support on the Programa Bolsa-Família (PBF). To achieve this goal, three studies were carried out. The first and second study aimed to adapt and apresent psychometric evidence of an instrument to measure racial prejudice in Brazil. The third study aimed analyze of the mediating role of racial prejudice in the relation between the skin color of the beneficial family’s and the level of support for this program. The results indicated the existence of nine items that are structured in three factors and, togheter, they explain 71.55% of the total variance. They were named as, a) Denial of Discrimination (α = 0.79); b) Accentuation of Intergroup Differences (α = 0.78) and c) Negation of positive emotions about black movement (α = 0.84). The second study aimed to perform the confirmatory factor analysis of the scale constructed in Study 1 and to analyze its convergent validity. The results of the two studies revealed a good fit to the three-factor model and satisfactory correlations between scales measuring the same construct. Finally, the Study 3 aimed to test the two hypothesis: 1) The mediating role of racial prejudice between the skin color of the family and the level of support for PBF; 2) The rejection of the PBF will be greater when the beneficiary family is black compared to the white Family. The analyses of mediation provide satisfactory empirical evidence for corroborating with the research hypothesis. On the other hand, the Descending Hierarchical Classification (CHD) pointed out that the participants' discourses showed positive evaluations of the PBF, but associated with criticisms about three aspects: failures in supervision, the program does not generate autonomy and the program makes families dependent on State